Screening of Fungicides and Botanicals for Controlling False Smut of Rice - MMP, Sumon; MS, Islam; KMM, Billah; SMA, Islam; MN, Jahan (Canadian Journal of Agriculture and Crops, 2022)
The present investigation was conducted in the field laboratory of the Department of Plant Pathology, Patuakhali Science and Technology University during August 2017 to December 2017 to evaluate the efficacy of botanicals viz., neem leaf extract, garlic clove extract, tulshi leaf extract and zinger rhizome extract at 10% concentration and fungicides viz., TALL 25EC, RAI 32.5 SC, TOWIN 50 WP, Syconazole 25SC and Y-Thane M-45 at 0.2% concentration to control rice false smut disease. The experiment was set up in a Randomized Complete Block Design (RCBD) with 3 replications. Among the treatments RAI 32.5 SC= Suspension concentrate and tulsi leaf extract performed better in respect of percent hill infection and it was 0.51%, 1.03%, 1.28% and 1.79% respectively at 85, 95, 105 and 115 days after transplanting (DAT). Result showed that the lowest percent plant and panicle infection at different days after transplanting were highest in the plot treated with RAI 32.5 SC followed by garlic extract. RAI 32.5 SC showed minimum percent infected grains which were 0.26%, 1.03% and 1.17% at 85, 105 and 115 DAT respectively and maximum 1.22%, 2.39% and 2.99% respectively, in the control plot at 85, 105, and 115 DAT. The highest thousand grain weight (114.6) and yield (4.790) were obtained in RAI 32.5 SC and the lowest thousand grain weight (108.3) and yield (3.587) harvested from the control plot.